2010
DOI: 10.1007/s11934-010-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Effects of Once-Daily Tadalafil in Men with LUTS Secondary to Clinical BPH

Abstract: Lower urinary tract symptoms (LUTS) are common and increase with age in men with benign prostatic hypertrophy (BPH). Erectile dysfunction (ED) also increases with age and is often a comorbid condition with BPH. Treatment with phosphodiesterase type 5 (PDE5) inhibitors aimed at decreasing breakdown of nitric oxide (NO) is a mainstay of treatment for ED. Because NO has been found to mediate male prostatic and urinary function in multiple ways, there is increasing interest in PDE5 inhibitors addressing concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…The presence of PDE‐5 has also been identified in tissues of the urogenital tract, such as the urinary bladder and prostate, and PDE‐5 appears to regulate smooth muscle tone of the bladder and prostatic urethra . It has been clinically demonstrated that PDE‐5 inhibitors have a beneficial effect on LUTS . In addition, NO synthase gene expression is reduced with aging in prostate tissue and may be a factor involved in the increased smooth muscle tone associated with LUTS .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PDE‐5 has also been identified in tissues of the urogenital tract, such as the urinary bladder and prostate, and PDE‐5 appears to regulate smooth muscle tone of the bladder and prostatic urethra . It has been clinically demonstrated that PDE‐5 inhibitors have a beneficial effect on LUTS . In addition, NO synthase gene expression is reduced with aging in prostate tissue and may be a factor involved in the increased smooth muscle tone associated with LUTS .…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation was found between sexual disorders and the severity of LUTS. Additionally, the relationship appeared to be independent of comorbidities such as hypercholesterolemia, hypertension, cardiac disease, and diabetes [14,15].…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 96%
“…Similarly, the bladder urothelium also releases NO in response to bladder distention, the target of which may be umbrella cells. There is also significant evidence for the NO-mediated smooth muscle relaxation in the prostate; however, in BPH models, the nitrigenergic innervation was reduced [14].…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%
“…There has been some concern that the beneficial effects of PDE5 inhibitors on LUTS may be associated with impairment of bladder function 19. This was addressed by a multicentre randomised double-blind placebo-controlled study that showed no statistically or clinically significant differences in urodynamic measures between tadalafil and placebo treatment groups 20…”
Section: What Is Tadalafil?mentioning
confidence: 99%